Comparison of Three-Port and Four-Port Laparoscopic Cholecystectomy: A Clinical Intervention Study - Torun, Mehmet (Scientific Reports in Medicine, 2025)
Objective: This study compares the outcomes of 3-port and 4-port laparoscopic cholecystectomy, evaluating differences in demographic factors, pain management, operative time, hospital stay, and recovery time.Methods: Conducted as a retrospective, randomized controlled study, data were gathered from 120 patients who underwent cholecystectomy at Van Başkale State Hospital. Patients were randomized into 3-port (n=60) and 4-port (n=60) groups. Preoperative antibiotic prophylaxis with cefazolin and postoperative pain management with diclofenac sodium were standardized. Variables analyzed included gender, surgical priority, VAS scores at 12 and 24 hours, operative time, hospitalization duration, and days to return to normal activities. Statistical significance was set at p